2022
DOI: 10.1177/08850666221103495
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors, and Prognosis of Bloodstream Infections in COVID-19 Patients in Intensive Care: A Single-Center Observational Study

Abstract: Background Critically ill COVID-19 patients are prone to bloodstream infections (BSIs). Aim To evaluate the incidence, risk factors, and prognosis of BSIs developing in COVID-19 patients in the intensive care unit (ICU). Methods Patients staying at least 48 h in ICU from 22 March 2020 to 25 May 2021 were included. Demographic, clinical, and laboratory data were analyzed. Results The median age of the sample (n  =  470) was 66 years (IQR 56.0-76.0), and 64% were male. The three most common comorbidities were hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…BSIs represent the second most frequent complication of COVID‐19 patients 43,44 and in our study, we found a rate of 21% for bacteremia and of 5.8% for fungemia.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…BSIs represent the second most frequent complication of COVID‐19 patients 43,44 and in our study, we found a rate of 21% for bacteremia and of 5.8% for fungemia.…”
Section: Discussionsupporting
confidence: 57%
“…The second most frequent fungal superinfections were attributed to C. albicans (10.6%), similar to other studies. 41,42 BSIs represent the second most frequent complication of COVID-19 patients 43,44 and in our study, we found a rate of 21% for bacteremia and of 5.8% for fungemia.…”
Section: Superinfections In Covid-19 Patientssupporting
confidence: 58%
“…In the present study, bloodstream infections were confirmed as the second most frequent infective complication, with a significant proportion being Gram-negative pathogens [ 21 , 53 , 54 ]. The elevated prevalence of Enterococcus spp.…”
Section: Discussionmentioning
confidence: 77%
“…The reported higher frequency of co-pathogen infections in COVID-19 patients admitted to ICU has been associated with various risk factors. In fact, in addition to the diffuse alveolar damage and the COVID-19-induced immunosuppressed state [ 20 ], ICU patients undergo several invasive procedures (such as endotracheal tube and venous catheter placement), are generally weaker due to the more severe form of illness, have more underlying comorbidities, and are treated longer with anti-inflammatory and antibiotic therapies, thus, resulting in extreme vulnerability and greater susceptibility to both bacterial and fungal infections [ 16 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both CR‐BSI and necrotizing pneumonia may be caused by MSSA 4,5 and empirical antibiotics might have masked the effect of the causative pathogens. It may therefore be difficult to determine which infection (CR‐BSI or necrotizing pneumonia) was the cause of the positive blood culture, even if we suppose that necrotizing pneumonia represented a secondary localization of bacteremia.…”
Section: Figurementioning
confidence: 99%